The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/admt.201900425
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Softlithography Using 3D‐Printed Molds

Abstract: most prevalent and conventional method for fabrication of PDMS-based microchips relies on softlithography, the main drawback of which is the preparation of a master mold which is costly and time-consuming. To prevent the attachment of PDMS to the master mold, silanization is necessary which can be detrimental for cellular studies. Also, using cell-compatible surfactant for mold coating adds extra pre-processing time. Recent advances in 3D printing have shown great promise in expediting the microfabrication pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 53 publications
0
45
0
Order By: Relevance
“…Inertial microfluidics exploits the interplay of focusing forces present within spiral microchannels, leveraging the variability in size and deformability of different cell types to perform high throughout cell separation. The microfluidic separation device used in this study was a 3D printed spiral microchannel, which was developed using previously reported fabrication methods 30 , 35 , 36 . This 3D printed microfluidic device not only allows for high throughout and efficient sperm recovery, but also presents new focusing behaviour for cells of a certain size, not seen in flexible PDMS microchannels.…”
Section: Resultsmentioning
confidence: 99%
“…Inertial microfluidics exploits the interplay of focusing forces present within spiral microchannels, leveraging the variability in size and deformability of different cell types to perform high throughout cell separation. The microfluidic separation device used in this study was a 3D printed spiral microchannel, which was developed using previously reported fabrication methods 30 , 35 , 36 . This 3D printed microfluidic device not only allows for high throughout and efficient sperm recovery, but also presents new focusing behaviour for cells of a certain size, not seen in flexible PDMS microchannels.…”
Section: Resultsmentioning
confidence: 99%
“…3D printing remains at an early stage development and with considerable potential for new innovation for the development of novel microfluidic and sensing systems [ 149 , 150 ]. It has been used for fabrication of moulds that have been used for PDMS casting of microfluidic devices [ 151 ]. Folch et al have demonstrated an interesting 3D printing approach for fabricating Quake-style microvalves and micropumps [ 152 ].…”
Section: Low-volume Productionmentioning
confidence: 99%
“…Different approaches have been studied in order to reduce the cost and increase the flexibility of fabrication of microfluidic devices. Some techniques completely bypassed the use of photolithography, using direct methods of microfabrication : to cite a few examples, micromilling [17], lost wax [18], 3D printing [19], electrophoresis [20]. Another perspective has focused on finding an easier and cheaper way to perform photolithography.…”
Section: Discussionmentioning
confidence: 99%